2014
DOI: 10.3171/2013.9.jns121924
|View full text |Cite
|
Sign up to set email alerts
|

Using intraoperative dynamic contrast-enhanced T1-weighted MRI to identify residual tumor in glioblastoma surgery

Abstract: Object The goal of surgery in high-grade gliomas is to maximize the resection of contrast-enhancing tumor without causing additional neurological deficits. Intraoperative MRI improves surgical results. However, when using contrast material intraoperatively, it may be difficult to differentiate between surgically induced enhancement and residual tumor. The purpose of this study was to assess the usefulness of intraoperative dynamic contrast-enhanced T1-weighted MRI to guide this differential diagnosis and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
1
18
0
2
Order By: Relevance
“…However, leakage of contrast agent and enhancement of reactive tissue might be misleading in T1 imaging with contrast enhancement [21]. More advanced techniques like T1-weighted dynamic contrast-enhanced MRI or 3D-spectroscopic imaging were recently applied to identify residual tumor in glioblastoma surgery under assistance of intraoperative MRI [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, leakage of contrast agent and enhancement of reactive tissue might be misleading in T1 imaging with contrast enhancement [21]. More advanced techniques like T1-weighted dynamic contrast-enhanced MRI or 3D-spectroscopic imaging were recently applied to identify residual tumor in glioblastoma surgery under assistance of intraoperative MRI [27].…”
Section: Discussionmentioning
confidence: 99%
“…Showing equal sensitivity ioMRI appears more specific in primary than in recurrent glioblastoma. cy of ioMRI in the future [27,29]. Dynamic contrast enhancement may provide better differentiation between contrast-enhancing tissue and leakage and DTI may reveal additional information about tumor margins [28].…”
Section: Discussionmentioning
confidence: 99%
“…It can be applied various times as it is independent of T1-effects after saturation, has proven to be as reliable as preoperatively performed DSC-MRI [8,9] and can distinguish residual tumor form surgically induced artefacts. Dynamic contrast-enhanced T1-weighted perfusion (DCE-MRI) has alternatively been used intraoperatively [10] . The beauty of this approach that requires more time than DSC-MRI (also at 3T) is that there is a by-product with the acquired T1-weighted images as the slope of contrast enhancement can easily be analyzed without the need for additional software.…”
Section: Topic Highlightmentioning
confidence: 99%
“…Thus, DCE-MRI measures contrast agent concentration as a function of time. Very recently, DCE-MRI was used intraoperatively at a 3 T MR scanner [10] . The used setup took 3 min and 45 s for the perfusion sequence.…”
Section: Dce-mrimentioning
confidence: 99%
“…[40,41] In addition, the time for image acquiring and the need of stop the surgery for it, prolong time of surgery and anesthesia. [42][43][44] Roder et al studied retrospectively 117 patients after conventional surgery, after 5-ALA, and after iMRI they found that mean residual tumor volume after iMRI-assisted surgery (0.5 [0.0e4.7] cm 3 ) was significantly smaller compared to the residual tumor volume after 5-ALAguided surgery (1.9 [0.0-13.2] cm 3 ; P = 0.022), which was significantly smaller than in conventional surgery (4.7 [0.0-30.6] cm 3 ; P = 0.007). Total resections were significantly more common in iMRI (74%) than in 5-ALAassisted (46%, P = 0.05) or conventional surgery (13%, P = 0.03).…”
mentioning
confidence: 99%